Analysis Black Spot on Tanjungpura - Imam Bonjol Road Section Pontianak using the Accident Equivalent Number Method - Widiyani, Agnes; Kadarini, S. Nurlaily; Sumiyattinah, Sumiyattinah (Fakultas Teknik Universitas Tanjungpura, 2025)
The increasing number of traffic accidents due to rapid population growth, inadequate road infrastructure, and low driver awareness poses a significant threat to public safety. This study aims to analyze the characteristics of traffic accidents and identify accident-prone areas (black sites) and points (black spots) along the Tanjungpura